The Influence of Tauhid Education on the Value of Cleanliness Responsibility in Early Childhood through the Slogan Hold, Save, and Collect - Aisah, Ai Siti; Sri Watini; Imamah (JURNAL PENA PAUD, 2025)
This research was inspired by the lack of awareness and responsibility regarding cleanliness among kindergarten children at Pos PAUD Sedap Malam 16, Cimahi City, as 24.39% of 41 children still littered and 19.51% did not return toys after use, indicating a need for a grip intervention. Most earlier studies have focused on habituation or environmental practices, and few have integrated a spirituality-based strategy; therefore, this study is novel in integrating monotheism (tauhid) education with the “Tahan, Simpan dan Pungut” (TSP) slogan, a combination not yet explicitly examined in prior theories. This research employed a quantitative approach using SEM-PLS, and all 41 children in group B were included in the sample. The results indicate that tauhid education influenced cleanliness responsibility (β = 0.942; p < 0.001) and the use of the TSP slogan (β = 0.914; p < 0.001). The presence of the TSP slogan also had a significant impact on cleanliness responsibility (β = 0.377; p = 0.013) and mediated the direct relationship between tauhid education and cleanliness responsibility (β = 0.345; p = 0.016), demonstrating that implementation of tauhid education, rather than the TSP slogan, effectively strengthens early childhood cleanliness responsibility.